Pemberdayaan Kelompok Peternak Itik Melalui Pemanfaatan Keong Sawah Sebagai Alternatif Pakan Itik di Dusun Cihateup, Tasikmalaya - Andri Kusmayadi; Siti Nurhidayah; Ulpah Jakiyah; Ristina Siti Sundari (Universitas Mathla'ul Anwar Banten, 2019)
EMPOWERMENT OF DUCK FARMERS GROUP THROUGH UTILIZATION OF RICE SNAILS AS ALTERNATIVE FEED FOR DUCKS IN CIHATEUP HAMLET, TASIKMALAYA. In Cihateup Hamlet, the presence of golden snail is abundant with a large number of paddy fields scattered in several locations. Moreover, the presence of golden snail in this area has the potential to be an agricultural pest so that to minimize its existence it needs to be used as an alternative to duck feed. The community service program aims to improve the insight and skills of members of livestock groups in utilizing and processing rice snails into quality food products. This community service method takes the form of counseling, training and mentoring for members of livestock groups. The target of this program is members of the livestock group “Kelompok Ternak Megar Bebek Cihateup”. The implementation of the community service program began in March to September 2017 in the Cihateup Hamlet, Sukanagalih Village, Rajapolah District, Tasikmalaya Regency. The impact of this program is to reduce the loss of rice farmers from rice snail pests and reduce the cost of feed for duck farmers. In addition, there has been an increase in the community's insight and skills in utilizing the region’s potential to become a useful and high-quality product.